2022
DOI: 10.1140/epjc/s10052-022-10061-1
|View full text |Cite
|
Sign up to set email alerts
|

Probing the axion–nucleon coupling with the next generation of axion helioscopes

Abstract: A finite axion–nucleon coupling, nearly unavoidable for QCD axions, leads to the production of axions via the thermal excitation and subsequent de-excitation of $$^{57}$$ 57 Fe isotopes in the sun. We revise the solar bound on this flux adopting the up to date emission rate, and investigate the sensitivity of the proposed International Axion Observatory IAXO and its intermediate stage BabyIAXO to detect these axions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 195 publications
(292 reference statements)
0
10
0
1
Order By: Relevance
“…It improves SNR by a factor > 10 4 and sensitivity in 𝑔 𝑎𝛾 by more than one order of magnitude [6], [8]. Furthermore, it has been recently shown that both IAXO and BabyIAXO will have the potential to detect solar axions from the 57 Fe nuclear transition at 14.4 keV [9]. Each of the relevant subsystems for BabyIAXO, namely magnet, optics and detector (Fig.…”
Section: A Fourth Generation Helioscope: Iaxo and Babyiaxomentioning
confidence: 99%
“…It improves SNR by a factor > 10 4 and sensitivity in 𝑔 𝑎𝛾 by more than one order of magnitude [6], [8]. Furthermore, it has been recently shown that both IAXO and BabyIAXO will have the potential to detect solar axions from the 57 Fe nuclear transition at 14.4 keV [9]. Each of the relevant subsystems for BabyIAXO, namely magnet, optics and detector (Fig.…”
Section: A Fourth Generation Helioscope: Iaxo and Babyiaxomentioning
confidence: 99%
“…Most of the axion related processes allowed in the Sun's interior could be differentiated with a dedicated detection setup at IAXO, allowing to distinguish different solar components produced by different mechanisms (see Figure 3). The proper measurement of those components would lead to an independent measure of axion couplings to photons, electrons, or even nucleons [122,123], shedding light on the full theoretical description of the axion.…”
Section: An Axion Observatorymentioning
confidence: 99%
“…Introduction.-Axions were originally introduced to solve the strong CP problem [1][2][3][4][5][6]. Current constraints on axions are based on a wide range of techniques, from laboratory experiments to astrophysics [6][7][8][9][10][11][12][13][14]. Bounds on the axion parameter space are obtained using helioscopes or haloscopes [7,[15][16][17][18][19][20][21], calculating axion emission in neutron stars (NSs) [22][23][24][25], and with other astrophysical and cosmological constraints [26][27][28][29][30][31][32][33].…”
mentioning
confidence: 99%